SEMIOTIC ANALYSIS OF KAONASHI'S CHARACTER TRANSFORMATION IN THE MOVIE SPIRITED AWAY BY HAYAO MIYAZAKI - Dinan Difitrian; Sukmawati Saleh (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This research aims to analyze the symbolism of Kaonashi's character in the animated film